The Response of Mule Ducks and Economic Implications when Fed at Different Times of Post Hatch - Williams , M.A.; Palmer, D.W.; Lallo, C.H.O.; Sundaram, V. (International Journal of Poultry Science, 2021)
Objective: This study aimed to evaluate the effect of early post hatch feeding on the growth performance and economic implication of Mule ducks. Materials and Methods: A total of 48 newly hatched Mule ducklings were used in this experiment. Economic principles such as average physical product (APP), marginal physical product (MPP), feed cost (FC), value of marginal product (VMP) and income over feed cost (IOFC) was calculated. The parameters investigated were total feed cost, revenue and margin over feed cost. Results: Treatments did not influence the APP, MPP, FC, VMP and IOFC over the 9 weeks period (p>0.050). IOFC was found to be negative from 7-9 weeks for all treatments. However, the relationship between the VMP and FC indicated that the VMP increased in a decreasing trend during the starter phase and between weeks 5 and 6 both were equal (VMP = FC). Conclusion: The theoretical relationship between the VMP and FC revealed that if finisher diet is fed from 6-9 weeks then the cost of the feed ingredient should not exceed 1.00TTD kg–1. The study suggested that a starter and grower feed should not be fed after 3 and 6 weeks; respectively. However, if production is to be continued until 9 weeks a finisher feed is recommended and cost of feed ingredients should not exceed 1.00TTD kg–1.